Problems of distance learning in virtual classrooms in teaching English in Deir Alla District Education Directorate from the point of view of teachers - Alghragheer, Ola Ayed Mohammad (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the problems of distance learning in the virtual classrooms in teaching English in the Directorate of Education of Deir Alla District from the teachers' point of view for the academic year 2021, and their number is (120) teachers, and the study sample was chosen by the simple random method. To achieve the objectives of the study, the researcher used the descriptive survey method and developed the study tool, which was a questionnaire consisting of (30) items. The validity and reliability of the study tool were confirmed and distributed to the study sample. After analyzing the data statistically, the study concluded with the following results that there are statistically significant differences at the significance level (α = 0.05) between the arithmetic averages of the estimates of English language teachers for the problems facing teachers and students in teaching students using virtual classes during distance learning due to the educational qualification variable in favor of a group Postgraduate studies, and the researcher attributes this to the knowledge of teachers who hold higher degrees with academic knowledge and the expansion of their knowledge in this category and with regard to the requirements and challenges facing distance learning and teaching of students in virtual classrooms. The researcher recommends designing and activating electronic courses by specialized committees, and supervising them by The Ministry of Education in order to bridge the gap in distance education for students and hold courses for students and train them on how to use it.
Keywords: distance learning; virtual classes; Problems of distance learning; Teacher of English